Perancangan Aplikasi Penulisan Tugas Akhir Fakultas Teknologi Informasi Universitas Atma Jaya Berbasis Web - Elisabeth (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2014)
The final project or undergraduate thesis is scientific papers that is a contribution to the development of science and is one of the requirements that must be met to obtain a Bachelor of arts degree (S-1) so that the content and writing needs to be arranged with certain procedures, including the use of scientific language and raw. Faculty of Information Technology at the University of Atma Jaya Makassar (FTI UAJM) has developed a guideline used as a reference for students to compose final project. But in practice, students who compose final project often have a variety of constraints in terms of both format writing, grammar and in outpour reporting results. This research uses a structured methodology while data collection was conducted using interviews with students and lecturers who become mentors and literature study conducted on Guidelines final project of FTI UAJM. The results of the implementation of this application minimizes the error rate of students in doing the final project.